Effects of hyperthyroidism and diabetes mellitus on spermatogenesis in peri- and post-pubertal mice - Shi, Hanhao; Korejo, Nazar Ali; Kamboh, Asghar Ali; Korejo, Rashid Ali; Shi, Fangxiong (Frontiers in Endocrinology, 2023)
Diabetes and thyroid dysfunction often co-exist. In our previous work, we elucidated the interactions of diabetes and hypothyroidism on testicular development and spermatogenesis.However, the present study illuminates the interface between diabetes and hyperthyroidism, where 16 ICR pregnant primiparous mice were used and subsequently 48 male pups were randomly selected (n=12/group) and separated into 4 groups: control (C), diabetic (D), diabetic + hyperthyroidism (DH) and hyperthyroidism (H). Computerized sperm analyses showed significant reductions in count by 20% and increases of 15% in D and H animals, respectively, vs. controls. However, rapid progressive sperm motility was significantly lower only in D (30%) compared with C mice. Our histomorphometric investigation depicted damaging effects on testicular and epididymal tissues; the stroma adjacent to the seminiferous tubules of the D mice revealed edematous fluid and unstructured material. However, in the epididymis, germ cell diminution contraction of tubules, compacted principal and clear cells, lipid vacuolization, atypical cellular connections, exfoliated epithelial cells, and round spermatids were conspicuous in DH mice. Collectively, our experiment was undertaken to ultimately better recognize male reproductive disorders in diabetic-hyperthyroid patients.